2021
DOI: 10.1038/s41551-021-00737-6
|View full text |Cite
|
Sign up to set email alerts
|

T cells armed with C-X-C chemokine receptor type 6 enhance adoptive cell therapy for pancreatic tumours

Abstract: The efficacy of adoptive cell therapy for solid tumours is hampered by the poor accumulation of the transferred T cells in tumour tissue. Here, we show that the forced expression of the C-X-C chemokine receptor type 6 (CXCR6, whose ligand is highly expressed by human and murine pancreatic cancer cells and by tumour-infiltrating immune cells) in antigen-specific T cells enhanced the recognition and lysis of pancreatic cancer cells and the efficacy of adoptive cell therapy for pancreatic cancer. In mice with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 85 publications
(94 reference statements)
0
81
0
1
Order By: Relevance
“…
Figure 2 Co-opting chemokine receptor axes to enhance trafficking of CAR-T cells into solid tumors Many tumors derived from different tissue origins share similar patterns of chemokine expression, raising the possibility of enhancing CAR-T cell infiltration into a diverse array of cancers using key chemokine/chemokine receptor axes. Chemokine receptors that have been utilized to guide T cell trafficking into solid tumors and specific anatomical niches include CXCR1, 66 CXCR2, 64 , 65 , 66 , 68 , 69 , 70 CXCR4 113 ( NCT04727008 ), CXCR6, 114 CCR2, 115 , 116 , 117 CCR4, 118 , 119 CCR8, 120 and CX3CR1. 121 Furthermore, CAR-T cells may be modified to express CCL19 and CCL21 to promote recruitment of endogenous DCs and T cells into tumors.
…”
Section: Enhancing Car-t Cell Infiltration Into Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…
Figure 2 Co-opting chemokine receptor axes to enhance trafficking of CAR-T cells into solid tumors Many tumors derived from different tissue origins share similar patterns of chemokine expression, raising the possibility of enhancing CAR-T cell infiltration into a diverse array of cancers using key chemokine/chemokine receptor axes. Chemokine receptors that have been utilized to guide T cell trafficking into solid tumors and specific anatomical niches include CXCR1, 66 CXCR2, 64 , 65 , 66 , 68 , 69 , 70 CXCR4 113 ( NCT04727008 ), CXCR6, 114 CCR2, 115 , 116 , 117 CCR4, 118 , 119 CCR8, 120 and CX3CR1. 121 Furthermore, CAR-T cells may be modified to express CCL19 and CCL21 to promote recruitment of endogenous DCs and T cells into tumors.
…”
Section: Enhancing Car-t Cell Infiltration Into Solid Tumorsmentioning
confidence: 99%
“… 130 , 131 Transmembrane CXCL16 mediates cell adhesion, whereas soluble CXCL16 acts as a chemoattractant. 114 As CXCL16 was found to be highly expressed by OVA-expressing murine pancreatic cancer models and patient pancreatic ductal adenocarcinoma (PDAC) tumor biopsies, OT-I cells, murine EpCAM-targeting CAR-T cells, and human mesothelin-targeting CAR-T cells were transduced to express CXCR6. CXCR6-transduced EpCAM-targeting CAR-T cells induced significant tumor regression with complete tumor rejection in 40% of mice, which was superior to the regression observed with unmodified control, CXCR3-transduced, or CCR4-transduced EpCAM-targeting CAR-T cells.…”
Section: Enhancing Car-t Cell Infiltration Into Solid Tumorsmentioning
confidence: 99%
“…Indeed, CCR8 and DNR-co-expressing CAR T cells showed even better efficacy against murine and human pancreatic cancers in mouse models. Similarly, Lesch et al ( 37 ) identified CXCL16 as an important chemokine secreted in murine pancreatic cancers, and their receptor CXCR6 was notably absent from cytotoxic T cells. Therefore, they engineered CAR T cells to co-express CXCR6 and demonstrated that these cells had both improved infiltration and killing of mouse subcutaneous pancreatic cancers, orthotopic pancreatic tumors, and patient-derived xenografts.…”
Section: Tumor Microenvironmentmentioning
confidence: 88%
“…Tumor stroma serves as a physical tumor barrier, and the immunosuppressive microenvironment hinders CAR T cells from successfully infiltrating into the tumor site. Regional delivery [ 30 , 31 ] and co-expression of fibroblast activation protein (FAP) [ 32 ], heparanase enzyme [ 33 ], or specific chemokine receptors [ 34 , 35 , 36 , 37 ] on CAR T cells represent potential strategies to improve migration and infiltration. Additional strategies have been developed to shield CAR T cells from inhibitory signals of the tumor microenvironment such as the co-expression of a dominant-negative receptor (DNR) for transforming growth factor beta (TGF-β) [ 37 , 38 , 39 , 40 ].…”
Section: Car T Cell Therapymentioning
confidence: 99%